Massive inclusion of digital technologies in schools : Argentinian young adolescents? appropriation of computers and the Internet in popular and middle classes - Benítez Larghi, Sebastián (2015)
Since the implementation of the Programa Conectar Igualdad (PCI) (Connecting Equality Program) in 2010 in Argentina, numerous Social Science specialists started to research how massive ICT introduction in schools would radically affect teaching and learning processes, knowledge building and youth behaviour. Nevertheless, there is still not much empirical evidence showing the ways in which these technologies are appropriated. This situation discloses the need of placing research questions locally situated with regard to those potential changes. What existing access methods does PCI encounter? And how does its implementation participate in the design of personal and family heterogeneous trajectories of ICTs appropriation? How do the students themselves perceive the infl uence of PCI on their own technologic abilities and competence? How do knowledge and aptitudes associated to new digital media articulate with the knowledge manners promoted by the school format and institutionalism? How does the massive introduction of netbooks affect the interaction among different school actors (students-teachers)? What happens in other sociability and socialization spaces, such as the house and cybercafé?